Apoptosis in response to heat stress is positively associated with heat-shock protein 90 expression in chicken myocardial cells in vitro - Zhang, Xiao-Hui (J Vet Sci, 2017)
To determine heat-shock protein (Hsp)90 expression is connected with cellular apoptotic response to heat stress and its mechanism, chicken (Gallus gallus) primary myocardial cells were treated with the Hsp90 promoter, aspirin, and its inhibitor, geldanamycin (GA), before heat stress. Cellular viability, heat-stressed apoptosis and reactive oxygen species level under different treatments were measured, and the expression of key proteins of the signaling pathway related to Hsp90 and their colocalization with Hsp90 were detected. The results showed that aspirin treatment increased the expression of protein kinase B (Akt), the signal transducer and activator of transcription (STAT)-3 and p-IKKα/β and the colocalization of Akt and STAT-3 with Hsp90 during heat stress, which was accompanied by improved viability and low apoptosis. GA significantly inhibited Akt expression and p-IKKα/β level, but not STAT-3 quantity, while the colocalization of Akt and STAT-3 with Hsp90 was weakened, followed by lower cell viability and higher apoptosis. Aspirin after GA treatment partially improved the stress response and apoptosis rate of tested cells caused by the recovery of Akt expression and colocalization, rather than the level of STAT-3 (including its co-localization with Hsp90) and p-IKKα/β. Therefore, Hsp90 expression has a positive effect on cellular capacity to resist heat-stressed injury and apoptosis. Moreover, inhibition of Hsp90 before stress partially attenuated its positive effects.